2006
DOI: 10.1128/mcb.26.9.3610-3624.2006
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Spermatogenic Cell Adhesion and Male Infertility in Mice Lacking TSLC1/IGSF4, an Immunoglobulin Superfamily Cell Adhesion Molecule

Abstract: TSLC1/IGSF4, an immunoglobulin superfamily molecule, is predominantly expressed in the brain, lungs, and testes and plays important roles in epithelial cell adhesion, cancer invasion, and synapse formation. We generated Tslc1/Igsf4-deficient mice by disrupting exon 1 of the gene and found that Tslc1 ؊/؊ mice were born with the expected Mendelian ratio but that Tslc1 ؊/؊ male mice were infertile. In 11-week-old adult Tslc1mice, the weight of a testis was 88% that in Tslc1 ؉/؉ mice, and the number of sperm in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 20 publications
2
60
1
1
Order By: Relevance
“…While targeted disruption of IGSF4 (TSLC1) on 11q23.2 has previ- ously been shown to lead to infertility in mice, suggesting an important role in spermatogenesis (Yamada et al, 2006), it has also been shown to be a tumor suppressor gene in both lung (Kuramochi et al, 2001) and ovarian cancer (Ehrlich et al, 2006). Interestingly, one of the other tumor suppressor genes that we identified, EPB41L3 on chromosome 18, is a known partner of TSLC1.…”
Section: Discussionmentioning
confidence: 88%
“…While targeted disruption of IGSF4 (TSLC1) on 11q23.2 has previ- ously been shown to lead to infertility in mice, suggesting an important role in spermatogenesis (Yamada et al, 2006), it has also been shown to be a tumor suppressor gene in both lung (Kuramochi et al, 2001) and ovarian cancer (Ehrlich et al, 2006). Interestingly, one of the other tumor suppressor genes that we identified, EPB41L3 on chromosome 18, is a known partner of TSLC1.…”
Section: Discussionmentioning
confidence: 88%
“…The Cadms (cell adhesion molecules) are a family of type I transmembrane proteins that have been described in several pathological and physiological processes such as the progression of lung and other cancers (reviewed in Murakami, 2005), mast cell adhesion (Ito et al, 2003(Ito et al, , 2007bFuruno et al, 2005;Ito and Oonuma, 2006), spermatogenesis (Wakayama et al, 2001;Wakayama et al, 2003;Fujita et al, 2006;van der Weyden et al, 2006;Yamada et al, 2006), epithelium development and homeostasis (Ito et al, 2007b), and central nervous system development (Biederer et al, 2002;Sara et al, 2005;Spiegel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is probably caused by a delay in the maturation of sperm cells, leading to an increase in apoptosis. The deficit in sperm cell maturation is due to an alteration of the adhesion between spermatogenic cells and the Sertoli cells Fujita et al, 2006;van der Weyden et al, 2006;Yamada et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Decreased expression of CADM1 has been associated with nonsmall cell lung cancer, 40 other solid tumors, [41][42][43][44] and with infertility in homozygous deficient transgenic mice. 39 Interestingly, ectopic expression of CADM1 has been associated with adult T-cell leukemia with the suggestion that it mediates binding of tumor cells to endothelium, thus facilitating tumor invasion. 45,46 A search of the literature failed to identify an evaluation for the presence of CADM1 in endothelial cells other than 2 articles, where it was not observed using immunohistochemistry in the pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…30,[35][36][37][38] CADM1 plays a variety of different roles in cell-cell adhesion. Examples of the disparate functions of CADM1 include basolateral adhesion of pulmonary epithelial cells, 30 organization of synapse formation, 35 adhesion of spermatogonia to Sertoli cells, 39 and adhesion of mast cells to nerve and smooth muscle cells. 37,38 Decreased expression of CADM1 has been associated with nonsmall cell lung cancer, 40 other solid tumors, [41][42][43][44] and with infertility in homozygous deficient transgenic mice.…”
Section: Discussionmentioning
confidence: 99%